The ways of improvement special physical training of high-qualified women volleyball players in competitive period of annual macrocycle - Malikova, A. N.; Doroshenko, E. Yu.; Symonik, A. V.; Tsarenko, E. V.; Veritov, A. I. (Physical Education of Students, 2018)
Purpose: to evaluate the influence of creating the program of training process in the competition period of the annual macrocycles on the level of special physical training of women volleyball players. Material: women volleyball players of high qualification participated in the experiment (n=14, age 20-22 years). An assessment of the level of special physical fitness of volleyball players was conducted. It is used author`s program. Results: features of the functional dependence of the level of general physical preparedness with the separate components of the special physical preparedness of volleyball players are established. The peculiarities of dynamics of indicators of athletes` special physical training in the competition period are determined. The strongest correlation relationship was the level of general physical fitness with: the level of general and hopping endurance; the level of development of jumping; special dexterity; special endurance; speed and strength of hands. As part of corrective modules, the training load of aerobic-anaerobic direction was increased. The main means of compound character training are: complex-coordinated and technical actions in combination with the accuracy of transmission; response to moving object; locking; attacking strikes. Conclusions: application of the experimental program of training process construction helps to maintain high level of basic indicators of athletes` special physical fitness during the competitive season. The experimental program involved the redistribution of training loads of aerobic and anaerobic-aerobic orientation within the framework of correcting modules.